2018
DOI: 10.1021/acsphotonics.8b00544
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon–Plasmon Interactions and Radiative Damping of Graphene Plasmons

Abstract: Understanding and controlling collective oscillations of electrons in graphene have enabled new classes of devices for deep subwavelength metamaterials, extraordinarily strong light−matter interactions, and nano-optoelectronic switches. Here, we demonstrate both theoretically and experimentally that the plasmon−plasmon and plasmon− radiation interactions modify strongly the plasmon resonance energy, radiative damping, and oscillator strength in graphene nanoribbon arrays. As the graphene filling factor approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…For example, it has been recently demonstrated that, at low temperature, monolayer MoSe 2 can achieve high reflection of incident light due to its excitonic resonance. , Additionally, the plasmonic resonances of graphene nanoribbons have been studied. Typically, reflection is not the primary point of interest, as the reflectivity is not particularly strong, with values under 20%. Related to our work, ref recently observed experimentally radiative rate enhancement in graphene nanoribbon array when the edges of the nanoribbons are brought together. Our work provides a theoretical understanding of this effect and indicates the implication of this effect for reflectivity enhancement.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…For example, it has been recently demonstrated that, at low temperature, monolayer MoSe 2 can achieve high reflection of incident light due to its excitonic resonance. , Additionally, the plasmonic resonances of graphene nanoribbons have been studied. Typically, reflection is not the primary point of interest, as the reflectivity is not particularly strong, with values under 20%. Related to our work, ref recently observed experimentally radiative rate enhancement in graphene nanoribbon array when the edges of the nanoribbons are brought together. Our work provides a theoretical understanding of this effect and indicates the implication of this effect for reflectivity enhancement.…”
supporting
confidence: 61%
“…x y y (8) and Maxwell's equations, we can use J x (x) to determine the H y and E x fields of the resonance. Moreover, the structure in Figure 1a is periodic with mirror symmetry about the center of the nanoribbon at x = 0.…”
mentioning
confidence: 99%
“…[18,19] The intrinsic quantum efficiencies of those graphene plasmonic devices are limited by the mismatched plasmonic dissipation rate and its coupling rate to the incident photonic mode. [19][20][21] The large plasmon dissipation rate is attributed to hot carrier scattering, dielectric losses to the substrate's phonons, and scattering from edge states or grain boundaries. [1,22]…”
Section: Introductionmentioning
confidence: 99%
“…[ 18,19 ] The intrinsic quantum efficiencies of those graphene plasmonic devices are limited by the mismatched plasmonic dissipation rate and its coupling rate to the incident photonic mode. [ 19–21 ] The large plasmon dissipation rate is attributed to hot carrier scattering, dielectric losses to the substrate's phonons, and scattering from edge states or grain boundaries. [ 1,22 ] To suppress the plasmonic dissipation channels, direct etching [ 23–25 ] and atop metal grating [ 12,14,15 ] are replaced by the patterned semiconductor substrates, [ 26 ] and the silicon oxide substrate is replaced by pristine boron nitride to eliminate electron–phonon coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] And for graphene metasurface, novel optical properties are dynamically tunable by changing the Fermi energy through voltage control or the changing intrinsic relaxation time through chemical doping. [23][24][25][26] Compared with metallic surface plasmons, graphene surface plasmons have the advantages of low loss, and high localization. 27 Thus, graphene will revolutionize metamaterials and metadevices, and promote the development of nano-optics.…”
Section: Introductionmentioning
confidence: 99%